Suicide bereavement: What succeeds after in the family? - Baños-Chaparro, Jonatan (2022)
Death by suicide is a painful and traumatic event for the family and social environment of the deceased. The literature refers that grief for suicide is totally different from grief for other types of death, being this type of grief more prolonged that involves psychological and physical problems, being necessary the support of health professionals. Therefore, a reflective analysis was developed on death by suicide and the various consequences that go through family members. The analysis of the study is organized into the following topics: the actions of family members after a suicidal event, the physical and psychological consequences, grief according to the stage of life and the importance of posvention as an intervention. In this sense, it is concluded that front facing the loss of a relative who committed suicide is particularly difficult compared to other types of death. The emotions they experience are more intense and the functioning and interaction between family members and, in turn, the social network, is affected. All it harm of this health, complicates the grieving process and interferes with the acquisition of adaptive behaviors.